Construction Of Simple Prototype Maglev Train Based On Review Of The Existing Experience - (:unkn) unknown (My University, 2025)
Magnetically-Levitating (??Maglev??) Train Technology Is A High-Speed Urban Transportation Solution Capable Of Contributing To Pollution Reduction And Energy Efficiency. The Objective Of The Project Is To Construct A Simple Prototype Maglev Train Based On Review Of The Existing Experience. It Is Proposed To Construct A Simple Prototype Maglev Train That Will Travel On The Test Track. To Construct The Simple Maglev Train Prototype We Use Simple Motor And Fan For Propulsion, Arranged Permanent Magnets For Stabilization And Levitation, Cement Fluid For Attachment, Glass For Guide And Compass For Identifying Pole Of The Magnets, Wood Stock For The Constructing Of Train And Track And The Prototype Maglev Train Is Done Based On Eds Technology. The Significance Of The Project Is To Give Some Hint On The Working Principle Of The Maglev Train And How It Constructs For The Coming Generation. Meanwhile, The Technology Has Transferred To Our Country So That The Transportation Sector Will Improve A Service In The Near Future. The Group Of The Project On Maglev??S Working Prototype Will Show Consumers, Investors, And Regulators That Maglev Technology Is A Smart Option For New Infrastructure Development.
Construction Of Simple Prototype Maglev Train Based On Review Of The Existing Experience